Secondary School Teachers' Educational Philosophies: Differences Regarding Work Experience, Type of School, and Education Programs - Sani Ćavar; Tonća Jukić (MDPI AG, 2024)
Teachers' educational philosophies have a great influence on teachers' actions in the classroom. They are partly influenced by the dominant pedagogical paradigm expressed in the strategic educational documents, but there are also some other factors that influence teachers' educational philosophies. This research aimed to determine secondary school teachers' educational philosophies and whether they differ in relation to a teacher's work experience, type of school, and educational program. A total of 355 secondary school teachers in Split-Dalmatia County in the Republic of Croatia participated in the research. The philosophy preference assessment scale consisting of two subscales (traditional and contemporary educational philosophies), was applied. The results showed that: secondary school teachers generally agreed more with contemporary than traditional educational philosophies; grammar school teachers agreed more with contemporary and vocational school teachers with traditional educational philosophies; the education program was a significant factor only for the subscale of traditional educational philosophies; and years of work experience was not a significant factor for either subscale. The results are discussed in the context of the relationship between teachers' educational philosophies, values, beliefs, and teaching experiences and the need for teachers to raise awareness of their educational philosophies and continuously compare and harmonise them with their educational practice.